Student Online Buying Behavior After Covid 19 In Medan, Indonesia - Lubis , Adelina; Effendi, Ihsan; Nasib, Nasib (International Journal of Science, Technology & Management, 2024)
At the time the Covid-19 pandemic had caused many changes to consumers, this was due to the limited movement of the community to carry out purchasing activities that were usually carried out before the pandemic. This research looks at the development of consumer behavior after the end of the Covid 19 pandemic among college students in the city of Medan. The framework of this research is the application to students' perceptions of online purchases with the dependent variable: Convenience, Privacy and security, Money, Save time and effort. This study directed is to understand consumers’ intention to purchase online shopping after the pandemic This study also uses three intervening variables, namely Perceived Ease of Use, Perceived Usefulness, and intention to use. This study aims to construct an online purchase model for university students in Medan. The subject of this study is a university in Medan. who uses online platforms to buy at online shops. This study was conducted with a sample of 291 respondents that uses online applications to buy products.